You Can’t Climb a Broken Ladder: Examining Underrepresentation of Multiply-Disadvantaged Groups in Secure and Senior Roles in UK Geochemistry - Pallavi Anand; Pieter Bots; Jessica Gagnon; Francis Appiah; Elena Maters; Shonil Bhagwat; Susan Little; Amy Riches; Ernest ChiFru; Anya Lawrence; Bryne Ngwenya (Earth Science, Systems and Society)
Geochemistry provides useful research tools related to fundamental processes in Earth, Environmental and Planetary Sciences. It has a distinct identity among the academic communities in these subjects, yet there is no specific data on workforce diversity among geochemists. We present the first demographic data of UK geochemists from a voluntary anonymous survey. We scrutinise the data with respect to protected characteristics (e.g., age, ethnicity, gender identity, sexual orientation and disability) and seniority of those within the community. We furthermore use this UK data to compare the career progression of geochemists who belong to multiply-privileged identities with those who belong to multiply-disadvantaged identities, to assess their representations with increased seniority on the academic career. This UK based case study on diversity and inclusion suggests that the career paths of geochemists belonging to multiple disadvantaged groups are restricted, including overrepresentation among those on fixed-term contracts or in service roles for laboratory support. Our data highlight that there is a decrease in diversity with an increase in seniority; specifically, UK geochemists from sexual and gender minorities, neurodiverse, and women from ethnic minority groups were not represented among the participants of our survey at the top of the academic ladder. There are many reasons for the loss of diversity in the UK geochemistry community with increased seniority. In order to address this and the underrepresentation of particular groups in senior leadership roles, our findings suggest that the career progression of geochemists requires an intersectional lens to examine the complexity of identity data. Such an approach would enable a better understanding of the impact of multiple and compounded disadvantages, biases, negative experiences and discrimination faced by multiply-disadvantaged identities.